ADVANCED METHODS FOR CLASSIFICATION QUALITY ASSESSMENT LEVERAGING ROC ANALYSIS AND MULTIDIMENSIONAL CONFUSION MATRIX - Chelak, Viktor; Hornostal, Oleksii; Chelak, Yehor; Gavrylenko, Svitlana (Сучасні інформаційні системи, 2025)
The object of the study is the process of classifying objects in scientific problems. The subject of the study is methods aimed at assessing the effectiveness of multiclass classification. The goal of the study is to study the classification process and develop a classifier evaluation module to increase the speed of such evaluation and reduce the time to build complex machine learning classifiers. Methods used: methods for evaluating machine learning classifiers, methods for constructing ROC curves, principles of parallel and distributed computing. Results obtained: an analytical review of the scope of application of the classification quality assessment module in the field of humanities, technical and economic sciences was conducted. Existing classification quality assessment metrics were considered and mathematical descriptions of metrics were formed for the multi-class case. Software was developed that implements the proposed mathematical descriptions using parallel calculations and optimization of identical operations. The developed module was tested for reliability. Conclusions. According to the results of the study, methods for effective classification quality assessment is proposed, which allows reducing the time for assessing the quality of multi-class classifiers by 40% compared to the classical methods. The development of this module opens up broad prospects for further research in the direction of improving the quality of classification, which will contribute to the development of various spheres of human activity and increase the efficiency of solving tasks related to data analysis.